Nasionalisme Relijius sebagai Strategi Dakwah Struktural - Subandi, Bambang (Proceedings of International Conference on Da'wa and Communication, 2019)
Structural Da'wa is characterized by strengthening the Da'wa message on the power structure. Religious nationalism is a form of structural Da'wa strategy appropriate for plural societies such as the Indonesian people. It emerged from resistance to colonization. In Indonesia, religious nationalism played a role in the formation of a constitution that formulated "a Godhead" as the basis of the State. The 1945 Constitution develops legal products that do not conflict with the message of Islamic Da'wa . Another role of religious nationalism is a network of tolerance based on justice by placing State sovereignty above religious sovereignty.